2013
DOI: 10.1016/j.febslet.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The genetic code as expressed through relationships between mRNA structure and protein function

Abstract: Structured RNA elements within messenger RNA often direct or modulate the cellular production of active proteins. As reviewed here, RNA structures have been discovered that govern nearly every step in protein production: mRNA production and stability; translation initiation, elongation, and termination; protein folding; and cellular localization. Regulatory RNA elements are common within RNAs from every domain of life. This growing body of RNA-mediated mechanisms continues to reveal new ways in which mRNA stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 104 publications
2
57
0
Order By: Relevance
“…of RNA structure and RNA-ligand interactions in most phases of gene regulation (Mauger et al 2013). Moreover, an accurate secondary structure model is critical for and can dramatically facilitate tertiary structure modeling (Hajdin et al 2010;Bailor et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of RNA structure and RNA-ligand interactions in most phases of gene regulation (Mauger et al 2013). Moreover, an accurate secondary structure model is critical for and can dramatically facilitate tertiary structure modeling (Hajdin et al 2010;Bailor et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Defining the secondary structure of an RNA is also a critical first step in tertiary structure modeling (Hajdin et al 2010;Weeks 2010;Bailor et al 2011). The structures of RNA molecules modulate the numerous functions of RNA and the interactions of RNAs with proteins, small molecules, and other RNAs in splicing, translation, and other regulatory machineries (Mauger et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Second, RNA is produced in a single-strand form, as opposed to a double-strand form, making it more accessible to a simple complementary antisense probe. While it is produced in a single-strand form, self-complementary sequences within the RNA form duplexes leading to a folded structure, much of which would be inaccessible to an antisense probe [36,37]. RNA also associates with proteins [38], which would also limit its accessibility to an antisense probe and also be initially produced and sequestered within the nucleus or mitochondria.…”
Section: Rna As a Biomarkermentioning
confidence: 99%
“…Four contributions cover RNA-related topics [24][25][26][27]. RNA structures are known to govern nearly every step in protein synthesis [24].…”
mentioning
confidence: 99%
“…RNA structures are known to govern nearly every step in protein synthesis [24]. Recent work suggested that some ribosomal subpopulations may have the property to influence the functions of the proteins they produce, and specific ribosomes were engineered to allow discrimination between different mRNA templates or with unique decoding properties [25].…”
mentioning
confidence: 99%